2013
DOI: 10.5714/cl.2013.14.2.099
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of aligned and length-controlled carbon nanotubes by chemical vapor deposition

Abstract: We investigated the effects of parametric synthesis conditions of catalysts such as sintering temperature, sorts of supports and compositions of catalysts on alignment and length-control of carbon nanotubes (CNTs) using catalyst powders. To obtain aligned CNTs, several parameters were changed such as amount of citric acid, calcination temperature of catalysts, and the sorts of supports using the combustion method as well as to prepare catalyst. CNTs with different lengths were synthesized as portions of molybd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Since multiwall carbon nanotubes (MWCNTs) possess high electrical conductivity, high thermal conductivity, and excellent mechanical properties [1][2][3], they have been extensively studied for being used in the electrical, thermal, and mechanical applications [4][5][6][7]. In order to achieve better characteristics of application products, the advancement in the synthesis technology has been tried to improve the properties of MWCNTs, including crystallinity, dispersibility, and purity [8][9][10]. Among these characteristics, purity is one of the most important properties from the viewpoint of better performance of application products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since multiwall carbon nanotubes (MWCNTs) possess high electrical conductivity, high thermal conductivity, and excellent mechanical properties [1][2][3], they have been extensively studied for being used in the electrical, thermal, and mechanical applications [4][5][6][7]. In order to achieve better characteristics of application products, the advancement in the synthesis technology has been tried to improve the properties of MWCNTs, including crystallinity, dispersibility, and purity [8][9][10]. Among these characteristics, purity is one of the most important properties from the viewpoint of better performance of application products.…”
Section: Introductionmentioning
confidence: 99%
“…The purity was evaluated from comparing -band to -band intensity ratio ( / ) of sample with / of reference materials. MWCNTs have been synthesized by either arcdischarge [18,19] or chemical vapor deposition (CVD) [1][2][3][4][5][6][7][8][9][10]. Since the MWCNTs synthesized by arc-discharge have higher crystallinity, -band is scarcely seen in the Raman spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…This method is particularly appealing because it is the most scalable and inexpensive deposition technique [5,6]. Graphene has been deposited via CVD on different transition metals (e.g., Pt [7], Pd [8], Re [9], Ni [10], Cu [3], Ru [11], Ir [12], Co [13], Rh [14], and W [15]), but very few groups have investigated the role of molybdenum (Mo) as a catalyst for graphene synthesis, despite that early studies showed that Mo may act as an effective catalyst for CNTs [16]. Also, using CVD, iron-Mo can act as a very efficient catalyst for the synthesis of single-walled and multi-walled CNTs [17].…”
Section: Introductionmentioning
confidence: 99%
“…By selecting the appropriate catalyst-substrate pair, one can produce CNTs of different types, such as horizontally/ vertically aligned, short/long, and crystalline/amorphous structures [5,13,20]. Moreover, in most previous studies, CNTs were produced on a small area of substrate, which could be made of silica, alumina, zeolite, or quartz.…”
Section: Introductionmentioning
confidence: 99%